Template-based growth of TiO₂ nanorods by sol-gel process - Sadeghzadeh-Attar, A.; Sasani Ghamsari, M.; Hajiesmaeilbaigi, F.; Mirdamadi, Sh. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
In this paper, the preparation of TiO2 nanorods by sol-gel-template process has been considered. The prepared sols were characterized by using FTIR spectroscopy, and the obtained nanorods were characterized by X-ray diffraction and SEM microscopy. SEM images show that TiO2 nanorods with uniform diameter of about 100-200 nm and a length of several micrometers. The results of XRD indicated that the TiO₂ nanorods were crystallized in the anatase and rutile phases after annealing to 400-700 ºC up to 2 hours.